Introduction to Frame Analysis First and Second Order Theories - Toniolo, Giandomenico (Springer Tracts in Civil Engineering,, 2019)
This textbook presents the principal methods of stress analysis for the design of frame structures, beginning with a description of the basic criteria for probabilistic safety verification used in modern codes. The Force Method and the Displacement Method are dealt with, together with their applications to more common structural situations. A special chapter is dedicated to the second order analysis required for slender structures and for the elaboration of instability problems. In turn, a thorough set of numerical examples rounds out the text. Given its scope, the book offers an ideal learning resource for students of Civil and Building Engineering and Architecture, and a valuable reference guide for practicing structural design professionals.